Aharonov-Bohm oscillations and weak antilocalization in topological insulator Sb2Te3 nanowires - Hamdou, Bacel; Gooth, Johannes; Dorn, August; Pippel, Eckhard; Nielsch, Kornelius (Applied Physics Letters, 2013)
Recently, it has been theoretically predicted that Sb2Te 3 and related materials are 3D topological insulators, a phase of matter that has a bulk bandgap and gapless electronic surface states protected by time-reversal symmetry. We report on low temperature magnetoresistance measurements on single crystalline Sb2Te3 nanowires with different cross sectional areas and high surface-to-volume ratios, synthesized via catalytic growth. The observation of Aharonov-Bohm oscillations and weak antilocalization indicates the presence of topological surface states. © 2013 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-20